The effect of student-perceived teacher support on math anxiety: chain mediation of teacher–student relationship and math self-efficacy - Wang, Chao; Xu, Qing; Fei, Wei-qun (Frontiers in Psychology, 2024)
Introduction This study investigates the mechanisms linking students’ perceived teacher support with math anxiety, focusing on the mediating roles of the teacher–student relationship and mathematics self-efficacy. Methods The research was conducted with 401 fifth-grade students in China, utilizing scales for Students’ Perceived Teacher Support, Teacher–Student Relationship, Math Self-Efficacy, and Math Anxiety. Results Findings revealed that student-perceived math teacher support, teacher–student relationship, and math self-efficacy were all significantly negatively correlated with math anxiety. It was notably found that student-perceived math teacher support influenced math anxiety through the chain mediation of teacher–student relationship and math self-efficacy. Additionally, the effect of students’ perceived emotional support from math teachers on math anxiety, mediated by teacher–student relationship intimacy, was significant only among male students. Discussion These results underscore the importance of fostering positive teacher–student interactions and enhancing self-efficacy to reduce math anxiety among primary school students. The gender-specific findings regarding emotional support and relationship intimacy highlight the need for tailored strategies in addressing math anxiety.